The Relationship Between Emotional Intelligence And Self- Efficacy Towards The Achievement Of Kurash Athletes In Lampung Province - Lupus Ilham Pratama; Frans Nurseto; Suwarli; Surisman (Jurnal Pendidikan Jasmani (JPJ), 2026)
This study aims to determine the relationship between emotional intelligence and self-efficacy on the achievements of Kurash athletes in Lampung Province. The method used is a survey method with a correlational approach. The research sample consisted of 25 people. The research instrument used was a questionnaire. Research hypothesis: 1) there is a relationship between emotional intelligence and athlete achievement, 2) there is a relationship between self-efficacy and athlete achievement, 3) there is a relationship between emotional intelligence and self efficacy and Kurash athlete achievement. The results of the study showed that: 1) there is a significant relationship between emotional intelligence and athlete achievement (r count = 0.443 > r table = 0.413), 2) there is a significant relationship between self-efficacy and athlete achievement (r count = 0.658 > r table = 0.413), 3) Simultaneously, emotional intelligence and self-efficacy towards athlete achievement (r count = 0.662 > r table = 0.413) with a contribution of 43.84%.